Measuring Cognition of Students with Disabilities Using Technology-Enabled Assessments: Recommendations for a National Research Agenda - Bechard, Sue; Sheinker, Jan; Abell, Rosemary; Barton, Karen; Burling, Kelly; Camacho, Christopher; Cameto, Renée; Haertel, Geneva; Hansen, Eric; Johnstone, Chris; et al. (The Journal of Technology, Learning and Assessment, 2010)
This paper represents one outcome from the Invitational Research Symposium on Technology-Enabled and Universally Designed Assessments, which examined technology-enabled assessments (TEA) and universal design (UD) as they relate to students with disabilities (SWD). It was developed to stimulate research into TEAs designed to better understand the pathways to achievement for the full range of the student population through enhanced measurement capabilities offered by TEA. This paper presents important questions in four critical areas that need to be addressed by research efforts to enhance the measurement of cognition for students with disabilities: (a) better measurement of achievement for students with unique cognitive pathways to learning, (b) how interactive-dynamic assessments can assist investigations into learning progressions, (c) improvement of the validity of assessments for students previously in the margins, and (d) the potential consequences of TEA for students with disabilities. The current efforts for educational reform provide a unique window for action, and test designers are encouraged to take advantage of new opportunities to use TEA in ways that were not possible with paper and pencil tests. Symposium participants describe how technology-enabled assessments have the potential to provide more diagnostic information about students from various assessment sources about progress toward learning targets, generate better information to guide instruction and identify areas of focus for professional development, and create assessments that are more inclusive and measure achievement with improved validity for all students, especially students with disabilities.